Educação das relações étnico-raciais : limites e possibilidades no curso de pedagogia da UFSCar - Cardoso, Ivanilda Amado (2016)
The social, historical, and legal requirements Education of ethnic racial ave provoked schools and universities to rethink their curriculum, management practices and pedagogical perspectives. In this scenario, teachers are considered agents of fundamental importance in overcoming racial asymmetries and in promoting quality education. But are teachers being prepared in initial teacher training courses to deal pedagogically with situations of racial discrimination and to value the racial and cultural diversity present in the school? Through this problematization, the research, whose results are present here, had the objective of analyze some aspects of the teacher education policy for the education of relations in the Pedagogy Course of UFSCar - São Carlos. The research was developed based on the qualitative approach and sought to carry out a descriptive, interpretative analysis of the context and of the collected materials-documents and interviews, with a view to the study of the policy of teacher training for the education of ethnic-racial relations, outlined by the case study procedures. We developed the analysis of these data focusing on the subjects' discourse and the social context in which they are inserted. The Course analyzed is limited to UFSCar, a unique institution in the debate of ethnic-racial relations in Brazil, due to the significant trajectory of the Nucleus of Afro-Brazilian Studies - NEAB in processes of teacher training for Education of ethnic-racial relations - ERER ; The presence of teachers working in the axes that contemplate the racial theme; And recognition of the university as a referential landmark in the state of São Paulo for the institutionalization of Affirmative Action policies for equal education for blacks, indigenous and students of public schools and specific vestibular for refugees. Thus, although the analysis , describe and interpret a context of political training in the UFSCar Pedagogy course, the results open lines of discussions to rethink and offer possible ways for the training of teachers in the perspective of ERER in Brazil, since the Historical processes, epistemology, conceptions and educational trends, government policies, civil society actions and other factors are implicated in the formation process.